Antecedents and consequences of work-related and personal bullying: A cross-sectional study in an Italian healthcare facility - Adelina Brizio; Paola Gatti; Daniela Acquadro Maran (Advances in Medicine, Psychology, and Public Health)
Introduction: Workplace bullying (WB), encompassing work-related bullying (WRB) and personal bullying (PB), significantly impacts workers and organizational culture. This study explores the broader implications of WB, focusing on its perception when associated with job functions versus when targeted at individuals. Methods: This cross-sectional study was carried out in a healthcare facility in northwestern Italy, involving 311 workers who responded to a questionnaire designed to assess the nature of bullying experienced. The survey explored various dimensions of WB, including psychosocial climate, leadership behavior, job satisfaction, and mental health outcomes. Results: Our findings indicated that WRB had a more detrimental impact than PB. Employees exposed to WRB reported lower job satisfaction (F(2, 295) = 59.048, p < .001), higher stress levels, and increased burnout (Emotional Exhaustion F(2, 294) = 40.346, p < .001). WRB was associated with negative perceptions of organizational fairness (F(2, 295) = 38.637, p < .001) and dynamism. PB also showed significant effects, particularly on team dynamics (MDOQ_team F(2, 294) = 52.514, p < .001) and communication (MDOQ_communic F(2, 294) = 15.038, p < .001). Discussion and Conclusions: WB profoundly deteriorates inter- and intra-group processes and undermines organizational culture, potentially affecting its legitimacy and reputation. The study underscores the need for organizational strategies that mitigate WB by promoting positive workplace environments and enhancing managerial practices to prevent bullying.